A Comprehensive Review of the Nutritional and Health-Promoting Properties of Edible Parts of Selected Cucurbitaceae Plants - Magdalena Borecka; Monika Karaś (Foods)
The Cucurbitaceae family includes commonly consumed plants such as pumpkin, watermelon, melon, horned melon, and cucumber, which are valued for their rich nutritional composition and health-promoting properties. These plants provide essential macronutrients, minerals, and bioactive compounds that contribute to their dietary and therapeutic significance. Particularly, Cucurbitaceae plants exhibit antidiabetic, hypolipidemic, antioxidant, and anticancer properties, making them valuable in addressing metabolic disorders and alleviating health risks associated with oxidative stress. This review aims to systematize current knowledge on selected cucurbits’ nutritional composition, mineral content, and phytochemical profile. It also examines their caloric value, glycemic index, and glycemic load, offering insight into their potential role in dietary strategies for patients with obesity, insulin resistance, or diabetes. Additionally, this review explores often-overlooked by-products, including seeds, leaves, and flowers, which are rich in bioactive compounds with potential health benefits. By compiling and analyzing existing data, this review highlights the nutritional and functional potential of Cucurbitaceae plants, reinforcing their significance in a health-promoting diet and disease prevention.